Adults with Cerebral Palsy Require Ongoing Neurologic Care: A Systematic Review. Issue 5 (26th February 2021) - Smith, Sarah E.; Gannotti, Mary; Hurvitz, Edward A.; Jensen, Frances E.; Krach, Linda E.; Kruer, Michael C.; Msall, Michael E.; Noritz, Garey; Rajan, Deepa S.; Aravamuthan, Bhooma R.
Abstract : Cerebral palsy (CP) neurologic care and research efforts typically focus on children. However, most people with CP are adults. Adults with CP are at increased risk of new neurologic conditions, such as stroke and myelopathy, that require ongoing neurologic surveillance to distinguish them from baseline motor impairments. Neurologic factors could also contribute to the motor function decline, chronic pain, and chronic fatigue that are commonly experienced by adults with CP. Based on a systematic literature review, we suggest (1) guidelines for neurologic surveillance and neurologist referral and (2) clinical research questions regarding the evolving neurologic risks for adults with CP. ANN NEUROL 2021;89:860–871